2007
DOI: 10.1111/j.1469-8137.2007.02016.x
|View full text |Cite
|
Sign up to set email alerts
|

Host effects on ectomycorrhizal fungal communities: insight from eight host species in mixed conifer–broadleaf forests

Abstract: Summary• To advance our understanding of host effects on the community structure of ectomycorrhizal fungi (EMF), EMF communities were compared among different host species, genera and families in two mixed conifer-broadleaf forests in Japan.• Using molecular identification methods we examined EMF root tips of eight coexisting species belonging to six genera (three families): Abies and Tsuga (Pinaceae), Betula and Carpinus (Betulaceae) and Fagus and Quercus (Fagaceae).• In total, 205 EMF species were detected, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
374
6
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 426 publications
(425 citation statements)
references
References 51 publications
41
374
6
4
Order By: Relevance
“…We recorded a total of 200 EM OTUs and the richness levels we observed in samples ranged from 4 to 46 and estimated total richness from 4 to 63, which is high but within the same range as other EM studies conducted in different ecosystems (e.g., Ishida et al. 2007; Aponte et al. 2010; Murata et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recorded a total of 200 EM OTUs and the richness levels we observed in samples ranged from 4 to 46 and estimated total richness from 4 to 63, which is high but within the same range as other EM studies conducted in different ecosystems (e.g., Ishida et al. 2007; Aponte et al. 2010; Murata et al.…”
Section: Discussionmentioning
confidence: 99%
“…Multihost studies in temperate mixed forests also revealed positive correlations between host taxonomic distance and the distinctiveness of the EM communities they support (Ishida et al. 2007; Morris et al. 2009; Murata et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the co-existence of different hosts enhances habitat diversity. With certain exceptions (Morris et al, 2008), host preference is rarely evident at the host species level, but is probably more important at higher taxonomic levels, that is, from genus to phylum (Ishida et al, 2007). While tropical forests are often dominated by a single ectomycorrhizal host lineage, such as the Dipterocarpaceae or certain groups of Fabaceae, temperate habitats are often composed of multiple codominant host lineages, for example, Fagales, Pinaceae and Salicaceae.…”
Section: Commentarymentioning
confidence: 99%
“…Plant taxa harbor different endophyte communities and therefore fungal diversity increases with host diversity (reviewed in Arnold, 2008). Similar patterns may enhance the diversity of ectomycorrhizal fungi (EcMF) in the temperate zone (Bruns et al, 2002;Ishida et al, 2007;Tedersoo et al, 2008), but the relevance of this and other potential factors remain unknown in tropical ecosystems because of a lack of published studies. In this issue of New Phytologist, address the biotic and abiotic factors driving the composition of an EcMF community in a Bornean rainforest that comprises one of the highest plant diversities in the world.…”
Section: New Phytologistmentioning
confidence: 99%